An application of cost benefit analysis to the strategic shipping sector - Mulvey, Charles (Statistical and Social Inquiry Society of Ireland, 1971)
This paper is derived from a cost benefit study of the involvement of the State in the shipping industry which was carried out in the context of the Appraisal of the Public Capital Programme. A brief theoretical comment on foreign exchange rates is the only new material I have added. The paper is concerned with the mainly strategic company in the state-owned shipping sector, Irish Shipping Ltd.(I.S.L.).
Read before the Society, 22 January 1971
Keywords: Cost benefit analysis; Shipping; Strategic shipping sector; Irish Shipping Ltd.; 314.15